Teacher self-efficacy and trust as mediators of instructional leadership effects on affective commitment: evidence from faith-based schools - Ali Mustopa; Dedi Arianto (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The present study examines the impact of instructional leadership on affective commitment among teachers in Islamic Senior High Schools, focusing on teacher self-efficacy and principal-teacher trust as mediating variables. The research was conducted at MAN 1 OKU Timur in South Sumatra, Indonesia, utilising a quantitative cross-sectional design and involving 87 teacher respondents. Data were collected through structured questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that instructional leadership has a significant and direct effect on affective commitment (β = 0.218, p < 0.01), as well as indirect effects mediated by teacher self-efficacy and principal-teacher trust. Principal-teacher trust emerged as the primary mediating mechanism, accounting for 47.2% of the total effect, while self-efficacy mediated 28.5%. Together, these mediators explained 56.4% of the overall influence. The results underscore that instructional leadership is fundamentally a relational process that fosters trust and professional confidence among teachers. This study contributes empirical evidence from an Islamic educational context and provides practical recommendations for leadership strategies to strengthen teacher commitment, enhance institutional performance, and improve educational outcomes in faith-based schools.